Efektivitas Hidroterapi Terhadap Peningkatan Kapasitas Fungsional Pasien Low Back Pain: Sebuah Studi Literatur. - Ihsan munqiz; Dini Nur Alpiah (JURNAL ILMIAH NUSANTARA, 2026)
Low Back Pain (LBP) has become a significant global health challenge, with incidence rates continuing to rise alongside an aging population. This condition is not merely a sensation of pain but a complex pathology that triggers long-term physical limitations and a drastic decline in quality of life. Clinically, the onset of LBP is often associated with intervertebral disc degeneration, such as Lumbar Disc Herniation (LDH), which causes nerve compression and disrupts motor and sensory functions in the lower body.The primary implication of LBP is the impairment of daily functional activities, where patients experience difficulties in basic mobility, such as bending or standing for extended periods. If not managed comprehensively, this disorder can progress into a chronic state and negatively impact the economic sector due to loss of work productivity. In the rehabilitation process, hydrotherapy or aquatic exercise emerges as an effective intervention option by utilizing the principle of buoyancy to reduce mechanical loads on the spinal joints. Additionally, hydrostatic effects and warm water temperatures help optimize blood circulation and promote muscle relaxation.